Theoretical Investigation of a Plasmonic Demultiplexer in MIM Waveguide Crossing with Multiple Side-Coupled Hexagonal Resonators - Yi-Yuan Xie; Chao He; Jia-Chao Li; Ting-Ting Song; Zhen-Dong Zhang; Qian-Ren Mao (IEEE Photonics Journal)
A novel plasmonic demultiplexer in metal–insulator–metal (MIM) waveguide crossing with multiple side-coupled hexagonal resonators is proposed and numerically investigated. The operating principle of the structure is analyzed by using the temporal coupled-mode theory. It is found that wavelength demultiplexing can be realized by modulating locations of resonators, which is validated by finite-difference time-domain (FDTD) simulations. In addition, the influences of structural parameters on transmission characteristics are studied by simulations. Simulation results reveal that the demultiplexed wavelength, transmission efficiency, and bandwidth of each channel can be manipulated by adjusting structural parameters of the demultiplexer. The proposed demultiplexer will provide an alternative for the design of highly integrated optical circuits and complex waveguide networks.